Merkel cell carcinoma: treatment and outcomes over a 10‐year period at a high‐volume academic center. (20th July 2021) - Nguyen, My‐Lien; Mohammad‐Zadeh, Ana; Krempl, Greg; Razaq, Mohammad; Collins, Lindsey; Zahoor, Talal; Zhao, Daniel; Henson, Christina
Abstract: Background: Merkel cell carcinoma (MCC) is a rare, highly aggressive malignancy which lacks high‐level evidence‐based treatment guidelines. Methods: To determine outcomes of MCC patients and assess the role of radiation in treatment, we performed a retrospective chart review of patients treated for MCC between 2006 and 2016 at a single high‐volume academic medical center. The primary outcome was overall survival (OS) for the entire population and for those populations receiving specific therapies. Results: Forty‐two patients were evaluable. OS for all patients was not reached since most remain alive at time of analysis. OS for the American Joint Committee on Cancer (AJCC) stage I was not reached. OS for stages II, III, and IV was 37.3 months (6.8, ‐), 49.5 months (14.2, 49.5), and 14.5 months (10.8, ‐), respectively. OS could not be reached in the high radiotherapy (RT) dose group (biologically equivalent dose [BED] ≥ 60) and was 49.5 months (10.8, ‐) in the low‐dose group (BED < 60). For surgical margin status, OS was 14.9158 months (6.8008, ‐) for positive margins and 37.3 months (10.8, ‐) for negative margins. Conclusions: No conclusive findings for OS were identified; however, trends for improved OS were associated with lower AJCC staging, negative surgical margins, and high RT doses.